Effects of proteinase inhibitors from Momordica cochinchinensis on several meat-spoilage bacteria - Loan, Tran Thi; Tran Chau, Pham Thi (Academia Journal of Biology, 2013)
This study aims at primarily investigating the effects of Momordica cochinchinensis proteinase inhibitors (MCoPIs) on several common meat-spoilage bacteria. The obtained results showed that the MCoPIs solution inhibited the growth of 4 studied bacteria: Bacillus cereus, Bacillus cereus 3, Bacillus cereus 81 and Escherichia coli. The proteinase activity (PA) of the bacterial broths supernatants reached the highest level after culturing 48-60 hrs, at 200 rpm and 37oC. The best PA of the studied bacteria was around pH = 7.6. Using PAG containing casein electrophoresis method, several clarified PA bands on dark blue ground were detected from broths supernatants of these bacteria. However, after treatment with MCoPIs solution most of these PA bands were less or disappeared. Treatment of meat with MCoPIs solution showed a positive effect on the freshness of meat. After 16hrs, only the meat samples treated with MCoPIs were remained fresh, while the control samples became rancid. Moreover, the soluble proteins as well as hydrolytic products from samples treated with MCoPIs solution were about 1,5-2 times lower than those of the corresponding control samples. The results indicated an applicable potentiality of MCoPIs solution for protection of meat from bacterial infection and prolonging meat freshness.